تحليل دور أستراتيجية الرسملة وأثرها في تطويرالقدرة الأئتمانية دراسة عينة من المصارف العراقية الخاصة للمدة (2002-2015) - HASSAN, MOHAMED SHAABAN; PETROS, DALIDA DAWOD (Journal of Duhok University, 2020)
The present study dealt with the analysis of the relationship between the banking capitalization strategy and the credit capacity within a sample of Iraqi private banks within the banking sector. The aim of this study is to try to identify the extent to which private banks operating in Iraq are practicing capitalization strategies or capital increase, and their impact on the development of banking credit services through analyzing the reality of private banking in Iraq and identifying the volume of credit granted by these banks. One of the most important conclusions of this study is the existence of a correlation relationship and a significant effect on the capitalization variable in the credit capacity variable for the surveyed banks. The research concluded that the increase in bank capital has appositive impact on the results of credit capacity .The study reached a set of proposals, the most important of which is that banks should study capitalization methods and follow the best methods that increase bank capital. Keywords: capitalization research, credit services, private banks, the banking system.